PMT Puding Buah Naga pada Bayi Sebagai Upaya Pencegahan Stunting di Desa Sambau Kepulauan Riau - Wulan Pramadhani; Indah Purnama Sari; Dea puspita; Farrah Azzahra; Fifi Trinita; Zanuba Bilqis; Syafrida Yanti (Compromise Journal Community Proffesional Service Journal, 2024)
Stunting is a chronic nutritional problem commonly occurring in children under five in developing countries, including Indonesia. Providing additional food to babies is the main strategy to prevent stunting from an early age. This activity aims to explore the practice and impact of providing additional food to babies as part of efforts to prevent stunting. The methods used were literature studies, location surveys, lectures, and demonstrations on making dragon fruit PMT. All community service activities have been carried out according to the schedule and planning. Community service activities were carried out in Sambau Village, Riau Islands, which were attended by cadres and several parents of toddlers and parents of stunted babies. Cadres and parents can find out what types of food can improve family nutrition, especially babies aged 6 monts-2 years who are malnourished or malnourished. By carrying out this activity, it is hoped that cadres and parents can practice what is taught to meet the nutritional value of babies at home.